Novel epiphytic root-fungus symbiosis in the Indo-Pacific seagrass Thalassodendron ciliatum from the Red Sea - Vohník, Martin; Josefiová, Jiřina (Mycorrhiza, 2024)
Symbioses with fungi are important and ubiquitous on dry land but underexplored in the sea. As yet only one seagrass has been shown to form a specific root-fungus symbiosis that resembles those occurring in terrestrial plants, namely the dominant long-lived Mediterranean species Posidonia oceanica (Alismatales: Posidoniaceae) forming a dark septate (DS) endophytic association with the ascomycete Posidoniomyces atricolor (Pleosporales: Aigialaceae). Using stereomicroscopy, light and scanning electron microscopy, and DNA cloning, here we describe a novel root-fungus symbiosis in the Indo-Pacific seagrass Thalassodendron ciliatum (Alismatales: Cymodoceaceae) from a site in the Gulf of Aqaba in the Red Sea. Similarly to P. oceanica, the mycobiont of T. ciliatum occurs more frequently in thinner roots that engage in nutrient uptake from the seabed and forms extensive hyphal mantles composed of DS hyphae on the root surface. Contrary to P. oceanica, the mycobiont occurs on the roots with root hairs and does not colonize its host intraradically. While the cloning revealed a relatively rich spectrum of fungi, they were mostly parasites or saprobes of uncertain origin and the identity of the mycobiont thus remains unknown. Symbioses of seagrasses with fungi are probably more frequent than previously thought, but their functioning and significance are unknown. Melanin present in DS hyphae slows down their decomposition and so is true for the colonized roots. DS fungi may in this way conserve organic detritus in the seagrasses' rhizosphere, thus contributing to blue carbon sequestration in seagrass meadows.
Keywords: symbióza; Dark septate endophytes; Necromass decomposition; Blue carbon sequestration; kořeny rostlin; Alismatales; Plant Roots; Ascomycota; Indický oceán; Epiphytism; Nutrient uptake; Root-fungus symbioses; Seagrasses; Symbiosis; Indian Ocean; Marine fungi